Kedai Kek Dan Roti Aishah / Siti Norbaya Mohamad ... [et al] - Mohamad, Siti Norbaya; Abdullah, Nur Syakirah; A Ghap Ar, Nurul Shahrin A; Ismail, Nawwar Najwa (2019)
We got the opportunity to study a small bakery which is 'Kedai Kek Dan Roti Aishah' in Kota Tinggi, Johor. In the first part of the case study, the general information of the shop has been collected. The information is gathered through verbal interview. It is a small family business that are selling variety of cakes, cookies and some bread. For the target market, younger customers may order pastries from a bakery, while families may drop by for bahulu, breads or cakes. The major problems of this bakery is lack of staff and poor marketing strategy. Every business have to design a strategy for achieving their goals", consisting of a marketing, business, and operational strategy. In this case study, we analyzed the strength, weaknesses, opportunities and threats of this bakery by using SWOT analysis. Thus, from the needs and demands from the customers of this company, we analysed the problems and provide recommendations on solution to overcome their problems and to fulfil their needs in Consumer Trend Canvas (CTC) analysis.